Digital creativity in dementia care support. (1st January 2013) - Zachos, Konstantinos; Maiden, Neil; Pitts, Kristine; Jones, Sara; Turner, Ian; Rose, Malcolm; Pudney, Kevin; MacManus, Julie
This paper reports the application of digital creativity to the care for people with dementia. A digital app was developed for use by staff in residential homes caring for people with dementia. The app invokes a set of computational services to undertake creative work, the results of which are presented to encourage and support cognitive creativity by care staff. The services undertake computational work such as retrieving resolutions to care problems encountered previously, matching care situations to situations in analogical domains such as parenting, teaching and prison life, and automatically generating customised creativity prompts. The app was designed so that care staff can generate contributions to resident care plans that are novel and hence individualised to the resident as part of a shift towards more person-centred care.